Spiritual Care Needs In Patients With Coronary Heart Disease : Literature Review - Aris Citra Wisuda; Tukimin; Citra Suraya (Jurnal Inspirasi Kesehatan, 2023)
Background: Coronary heart disease continues to have a significant mortality rate mortality rate of up to 72.14% annually. Patients who have this disease also struggle to fulfill their basic needs, particularly their spiritual demands. In order for patients to experience a higher quality of life, it is crucial to meet their spiritual requirements. Objective: This study aims to determine the spiritual needs of patients with coronary heart disease. Methods: The Literature review was carried out through Google Scholar and PubMed. The keywords used in were English incuding “Cronic illnes” AND “Spiritual Needs” OR “Spiritual” NOT “Sprirituality” AND “Coronary Heart Disease” OR “Ischemic heart disease” OR “Coronary artery disease” AND “qualitative”. The study employed qualitative method. Result: The spiritual need of the relationship dimension with oneself was acceptance of the past. The spiritual need from the dimension of relationships with other people was the support from friends, partners or family. The spiritual need from the dimension of relationship with nature was the availability of a comfortable environment. The need for the dimension of relationship with God was gratitude for the life one has. Conclusion: Patients with coronary heart disease must have their spiritual needs met in order to cope with their illness and have a better quality of life.